(untitled) (Third Sector Social Economic Review, 2024)
The load capacity factor (LCF), recently developed, takes into account not only demand side (consumption) but also supply side (biocapacity) of nature. Therefore, it is seen that LCF has started to be used in recent studies in environmental economics literature. In this context, the study aims to test long-run effect of economic growth, environmental technologies and energy consumption on LCF in Turkey. For this purpose, annual data for the period 1974-2019 are tested with Fourier-based time series techniques (ADF, ADL and FMOLS). In addition, long-run robustness test of study is also tested with Fourier-based DOLS and CCR techniques. The empirical findings of study show that economic growth and energy consumption, as expected, harm environmental pollution and consequently environmental quality. Moreover, contrary to expectations, findings reveal that environmental technologies have negative impact on environmental quality. Therefore, policy makers in Turkey should urgently implement some important policies to improve environmental quality. For this, policymakers should take steps to invest more renewable energy sources and environmental technologies. In addition, necessary steps should be taken for establishment of green growth. Finally, protocols should be signed with stakeholders to reduce the use of non-renewable energy sources, and non-compliance with these protocols should not be tolerated.